2017
DOI: 10.1080/13561820.2017.1315060
|View full text |Cite
|
Sign up to set email alerts
|

Current state of interprofessional education in Canadian medical schools: Findings from a national survey

Abstract: Interprofessional education (IPE) is being increasingly recognised and prioritised in undergraduate medical education. While efforts are underway to integrate IPE into health professional curricula across Canada, the state of IPE in Canadian medical schools remains unclear. This study aims to assess the current practice of IPE in Canadian undergraduate medical curricula. An online survey was distributed to IPE directors (or designees) of all Canadian medical schools. The survey gathered details of the IPE expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…On the other hand, there is also a high prevalence of using the "problem-posing education" approach developed by Paulo Freire in both medical and physical therapy schools. That is a striking characteristic of IPE in Brasil, as international studies have shown that the main strategies used are problem-based learning, simulation, and case-based discussions 4,11 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, there is also a high prevalence of using the "problem-posing education" approach developed by Paulo Freire in both medical and physical therapy schools. That is a striking characteristic of IPE in Brasil, as international studies have shown that the main strategies used are problem-based learning, simulation, and case-based discussions 4,11 .…”
Section: Discussionmentioning
confidence: 98%
“…Descriptive analysis describing the schools' characteristics and the details of IPE activities in MD and PT courses was carried out using frequency, percentage, main barriers to implementing IPE are restrictions in the curriculum, lack of planning, lack of resources, communication among different professions, large class size, and stereotypes 4,5,8 .…”
Section: Discussionmentioning
confidence: 99%
“…When surveyed, dental faculty and students often report a positive attitude towards IPE, but go on to share the need for authentic experiences; constructive, faculty‐led clinical environments; and important small group work . In a recent survey of Canadian undergraduate medical schools, both faculty and students reported interest in moving forward with the integration of IPE into medical education . Unfortunately, as with many IPE studies, the Canadian respondents reported implementation barriers including issues with scheduling and funding limitations for actual implementation.…”
Section: Overviewmentioning
confidence: 99%
“…8,9 In a recent survey of Canadian undergraduate medical schools, both faculty and students reported interest in moving forward with the integration of IPE into medical education. 10 Unfortunately, as with many IPE studies, the Canadian respondents reported implementation barriers including issues with scheduling and funding limitations for actual implementation. Although healthcare educators affirm the value of collaborative care, the complexity of integrating multiple disciplines across multiple units continues to be daunting for many.…”
mentioning
confidence: 99%
“…In the US, IPE courses and clinical IPE training were provided in 92% and 89% of academic health centers in 2010, respectively (Greer et al 2014). In Canada, IPE is provided in 12 of 17 medical schools (You et al 2017). In Japan, a 2016 survey targeting all 81 medical school in Japan (response rate 79.0%) showed that IPE courses were provided in 46, of which 41 were compulsory.…”
Section: Introductionmentioning
confidence: 99%